Effect of alkohols as hardening-accelerating admixtures on the cement properties - Флейшер, Ганна Юріївна; Токарчук, Володимир Володимирович; Василькевич, Олександр Іванович; Свідерський, Валентин Анатолійович (Technology audit and production reserves, 2014)
The effect of alcohols as hardening-accelerating admixtures on physicomechanical properties of cement, particularly strength indexes in early hardening period is investigated. Alcohols can be used as an effective hardening accelerators of cement. The effectiveness of the influence of alcohols on the cement properties depends on their spatial structure and the number of hydroxyl groups. It was found that the largest increase in the cement strength is promoted by individual admixtures of alcohols with 2-3 hydroxyl groups (ethylene glycol and glycerol). Comparative analysis has revealed that alcohols behave as hardening accelerators only in the early periods (up to 3 days, especially on the 1st day), and known and widely used accelerator - calcium chloride, on the contrary, has no influence on the strength development on the 1st day of hardening, but contributes to a significant increase in strength on the 3-28 day. It was found that alcohols can be used as components of complex additives. The influence of alcohol on the cement strength in the complex additive “superplasticizer + hardening accelerator” was studied. It was found that the effectiveness of alcohols as accelerators is strongly affected by the components of complex additives since the best results were in modifying superplasticizer by ethanol, which had no significant effect on the cement strength as an individual additive. Alcohols are effective chemical additives that can be used as hardening accelerators, both individually, and as part of multi-component additives.